2019
DOI: 10.1016/j.ejrad.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of radiation dose and low contrast detail detectability using routine paediatric chest radiography protocols

Abstract: Comparative analysis of radiation dose and low contrast detail detectability using routine paediatric chest radiography protocols Objectives: To compare low contrast detail (LCD) detectability and radiation dose for routine paediatric chest X-ray (CXR) imaging protocols among various hospitals. Methods: CDRAD 2.0 phantom and medical grade polymethyl methacrylate (PMMA) slabs were used to simulate the chest region of four different paediatric age groups. Radiographic acquisitions were undertaken on 17 X-ray mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Moreover, a physical IQ method was used for calculating IQF inv using CDRAD 2.0 analyser software which offers high reliability and is unaffected by differences in human eyesight and experience 16 . The CDRAD 2.0 phantom and IQF inv measurements have been used widely for optimization studies and when comparing different DR detector types 17–20 . Studies reported a strong relationship with visual IQ when evaluating lesion visibility, especially for CXR 21–23 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a physical IQ method was used for calculating IQF inv using CDRAD 2.0 analyser software which offers high reliability and is unaffected by differences in human eyesight and experience 16 . The CDRAD 2.0 phantom and IQF inv measurements have been used widely for optimization studies and when comparing different DR detector types 17–20 . Studies reported a strong relationship with visual IQ when evaluating lesion visibility, especially for CXR 21–23 …”
Section: Methodsmentioning
confidence: 99%
“…16 The CDRAD 2.0 phantom and IQF inv measurements have been used widely for optimization studies and when comparing different DR detector types. [17][18][19][20] Studies reported a strong relationship with visual IQ when evaluating lesion visibility, especially for CXR. [21][22][23] The radiation dose recorded from Dose Area Product (DAP) was measured three times for each exposure to reduce random error.…”
Section: Image Quality Evaluation and Dose Measurementmentioning
confidence: 99%